Relationship between physical exercise practice and associated factors to motivational regulations of Brazilians adolescents Relação da prática de exercícios físicos e fatores associados às regulações motivacionais de adolescentes brasileiros - Silva R.B.* (2012)
Based on Self-Determination Theory (SDT; Deci & Ryan, 1985), this study investigated the relationship between physical exercise, motivational regulations and associated factors in adolescents. We conducted a cross-sectional study involving 471 adolescents aged 14 to 18 years old, students at a public school in Florianópolis/SC, Brazil. Questionnaires were used to conduct the survey and the data was analyzed by descriptive and inferential statistics. Boys were more active and more self-determined for physical exercise than girls. For both genders the internal motivations and the self-determination were positively associated with physical exercise. The older and overweight girls had higher identified regulation. Among boys, students who are overweight were more amotivated and less intrinsically motivated. All students, adolescents who are studying in the afternoon period showed a higher baseline of self-determination. The study concluded that adolescents more self-determined did more physical exercise regularly. Also the study showed that there are factors associated with the motivational regulations and that there are differences between girls and boys. © FTCD/FIP-MOC.